Plato and Jesus, Not Caesar : Metaphysics of Freedom and Tyranny in Younger Europe - Stróżyński, Mateusz (Brill's Studies in Intellectual History, 2026)
This book discusses the influence of ancient and medieval Platonism and Christian Platonism on the modern political concepts and experiences of freedom and tyranny in Central-Eastern Europe. The main claim of the book is that because the nations of Younger Europe were oppressed by the imperialism of Russia, Germany, and Austria, they maintained a stronger connection to the premodern, Christian Platonic tradition. This tradition was experienced as a source of inspiration in the struggle for freedom and independence. The book focuses on the life and work of selected philosophers, poets, and artists, all of whom were both mystics and figures deeply engaged in their nations' fight for freedom.